Ligand-independent traffic of Notch buffers activated Armadillo in Drosophila. - Sanders, P.G.; Muñoz-Descalzo, S.; Balayo, T.; Wirtz-Peitz, F.; Hayward, P.; Arias, A.M. (PLoS Biology, 2009)
Notch receptors act as ligand-dependent membrane-tethered transcription factors with a prominent role in binary cell fate decisions during development, which is conserved across species. In addition there is increasing evidence for other functions of Notch, particularly in connection with Wnt signalling: Notch is able to modulate the activity of Armadillo/ss-catenin, the effector of Wnt signalling, in a manner that is independent of its transcriptional activity. Here we explore the mechanism of this interaction in the epithelium of the Drosophila imaginal discs and find that it is mediated by the ligand-independent endocytosis and traffic of the Notch receptor. Our results show that Notch associates with Armadillo near the adherens junctions and that it is rapidly endocytosed promoting the traffic of an activated form of Armadillo into endosomal compartments, where it may be degraded. As Notch has the ability to interact with and downregulate activated forms of Armadillo, it is possible that in vivo Notch regulates the transcriptionally competent pool of Armadillo. These interactions reveal a previously unknown activity of Notch, which serves to buffer the function of activated Armadillo and might underlie some of its transcription-independent effects.